Virtual twins for model‐informed precision dosing of clozapine in patients with treatment‐resistant schizophrenia - Sam Mostafa; Reza Rafizadeh; Thomas M. Polasek; Chad A. Bousman; Amin Rostami‐Hodjegan; Robert Stowe; Prescilla Carrion; Leslie J. Sheffield; Carl M. J. Kirkpatrick (Wiley, 2024)
Abstract Model‐informed precision dosing using virtual twins (MIPD‐VTs) is an emerging strategy to predict target drug concentrations in clinical practice. Using a high virtualization MIPD‐VT approach (Simcyp version 21), we predicted the steady‐state clozapine concentration and clozapine dosage range to achieve a target concentration of 350 to 600 ng/mL in hospitalized patients with treatment‐resistant schizophrenia (N = 11). We confirmed that high virtualization MIPD‐VT can reasonably predict clozapine concentrations in individual patients with a coefficient of determination (R2) ranging between 0.29 and 0.60. Importantly, our approach predicted the final dosage range to achieve the desired target clozapine concentrations in 73% of patients. In two thirds of patients treated with fluvoxamine augmentation, steady‐state clozapine concentrations were overpredicted two to four‐fold. This work supports the application of a high virtualization MIPD‐VT approach to inform the titration of clozapine doses in clinical practice. However, refinement is required to improve the prediction of pharmacokinetic drug-drug interactions, particularly with fluvoxamine augmentation.